Arnold Zweig correspondence and writings - Zweig, Arnold, 1887-1968.
TLS (1956 June 6) from Zweig to Walter Zadek, ALS (1938 May 6) from Zweig to M. Eitingon, and writings by Zweig on Sigmund Freud, Solomon, and Benedictus de Spinoza.
Photocopies, in part.
Novelist and essayist.
Collection material in German.
Forms part of: Sigmund Freud collection.
Keywords: Eitingon, M. -- 1880-1943 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Solomon, -- King of Israel; Spinoza, Benedictus de, -- 1632-1677.; Zadek, Walter -- Correspondence; Psychoanalysis; Essayists; Novelists